Application of metallic phytates to poly(vinyl chloride) as efficient biobased phosphorous flame retardants. Issue 33 (6th May 2018) - Cheng, Luyao; Wu, Weihong; Meng, Weihua; Xu, Shuo; Han, Hongda; Yu, Yongfang; Qu, Hongqiang; Xu, Jianzhong
ABSTRACT: Simple, direct precipitation was used to synthesize green, renewable, biobased flame retardants. Copper phytate (Cu–Phyt), zinc phytate, aluminum phytate, and tin phytate (Sn–Phyt) were synthesized. Thermogravimetric analysis performed in N2 revealed that the metallic phytate (M–Phyt, where M is Cu, Zn, Al, or Sn) salts showed good charring. The limiting oxygen index (LOI), cone calorimetry (CONE) test data, tensile strength, and impact toughness were measured for flexible poly(vinyl chloride) (PVC) containing 15 wt % M–Phyt salts. The PVC/Sn–Phyt LOI rose from 24.9 to 30.3%, and the PVC/Sn–Phyt mechanical properties were on par with those of the pure PVC. The CONE test results indicate that PVC/Cu–Phyt showed the lowest total smoke production (TSP) and peak heat‐release rate (pHRR) among the samples. The TSP and pHRR of PVC/Cu–Phyt were 15.77 m 2 and 181.77 kW/m 2, respectively, 62.63 and 44.48% lower than those of the neat PVC. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 46601. Abstract :